EDUKASI ANAK ATASI BENCANA ALAM MELALUI PENGEMBANGAN MEMO SINCAN (MEDIA MONOPOLY ATASI BENCANA ALAM) - Rica Wijayanti; Yusrianto Sholeh; Yunita Hariyani (Jurnal Muara Pendidikan, 2024)
Natural disasters are natural events that can occur at any time and place, often without prior warning. Therefore, it is crucial to educate children from an early age to prepare them for when natural disasters occur. One way to educate children about disaster preparedness is by developing the MEMO SINCAN educational media. This activity aims to produce a learning media product in the form of the MEMO SINCAN game. This method involves developing the MEMO SINCAN game media using the ADDIE design model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. The instruments used include validation sheets, questionnaires, and test sheets. The data analysis results concluded that using the MEMO SINCAN game media increased children's understanding of natural disasters by 76.67%. This finding indicates that the development of the MEMO SINCAN game media is highly effective in improving learning outcomes.